2021
DOI: 10.3390/pharmaceutics13050747
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Dual-Targeting Therapeutic Mechanism of Epidermal Growth Factor Receptor (EGFR) Based on Reversed Allosteric Communication

Abstract: Dual-targeting therapeutics by coadministration of allosteric and orthosteric drugs is drawing increased attention as a revolutionary strategy for overcoming the drug-resistance problems. It was further observed that the occupation of orthosteric sites by therapeutics agents has the potential to enhance allosteric ligand binding, which leads to improved potency of allosteric drugs. Epidermal growth factor receptor (EGFR), as one of the most critical anti-cancer targets belonging to the receptor tyrosine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 88 publications
1
22
0
Order By: Relevance
“…However, in both the wild-type lorlatinib- and gilteritinib-bound states, the N-lobe (residues 1,093–1,203) showed enhanced anti-correlated motions with the C-lobe (resdues 1,204–1,401) compared to both the double mutant states ( Supplementary Figure S4 ). This pattern of the anti-correlated motions between the N- and C-lobes has been previously reported in MD simulations of other protein kinases such as protein kinase A ( Masterson et al, 2011 ), glycogen synthase kinase 3β ( Lu et al, 2011 ), and EGFR ( Qiu et al, 2021 ). Collectively, the CC ij analysis indicated that the double mutations I1171N/F1174I decreased the anti-correlated motions between the N- and C-lobes of ALK kinase domain.…”
Section: Results and Discssionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, in both the wild-type lorlatinib- and gilteritinib-bound states, the N-lobe (residues 1,093–1,203) showed enhanced anti-correlated motions with the C-lobe (resdues 1,204–1,401) compared to both the double mutant states ( Supplementary Figure S4 ). This pattern of the anti-correlated motions between the N- and C-lobes has been previously reported in MD simulations of other protein kinases such as protein kinase A ( Masterson et al, 2011 ), glycogen synthase kinase 3β ( Lu et al, 2011 ), and EGFR ( Qiu et al, 2021 ). Collectively, the CC ij analysis indicated that the double mutations I1171N/F1174I decreased the anti-correlated motions between the N- and C-lobes of ALK kinase domain.…”
Section: Results and Discssionsupporting
confidence: 77%
“…The gilteritinib was extracted from the 4JQR structure, and we then employed molecular docking method to dock gilteritinib into the ALK active site using the crystal structure of ALK–lorlatinib complex (PDB ID: 4CLI) ( Johnson et al, 2014 ). Molecular docking method has been widely used to model previously unknown protein kinase/enzyme–ligand interactions such as epidermal growth factor receptor (EFGR)–osimertinib ( Qiu et al, 2021 ), angiotension-converting 2 (ACE2)–puerarin/quercetin ( Pan et al, 2020 ), proliferator activated receptor γ (PPARγ)–bavachinin ( Feng et al, 2021 ), and sirtuin 6 (SIRT6)–JYQ-42 interactions ( Zhang et al, 2021 ).…”
Section: Results and Discssionmentioning
confidence: 99%
“…With the significant progresses in biophysics and bioinformatics, computational exploration of allosteric sites has prominently boosted rational allosteric drug design 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 . The reversed allosteric communication, namely orthosteric perturbations induce the emergence of allosteric sites, has been exemplified in the exchange protein activated by cAMP isoform 1 (EPAC1), 15-lipoxygenase and phosphoinositide-dependent protein kinase 1 (PDK1).…”
Section: Discussionmentioning
confidence: 99%
“…To describe and investigate residue-residue interactions within biomolecular systems, we employed concepts from network theories [108] , [109] , [110] , [111] . The whole ribonucleotide protein complex was defined as a set of nodes, which were assigned to the Cα atom within each amino acid residue or P atom in the nucleotide backbone for each nucleotide.…”
Section: Methodsmentioning
confidence: 99%